Optimización de los procesos en la modalidad de libre contratación de la cooperativa de taxis de servicio interparroquial de la ciudad de Loja, utilizando tecnologías de la información. - Carpio Ortega, Jossed Efren (2021)
Currently, the use of information systems allows optimizing the way of managing information and improving the quality in the provision of services, combining technology with a service that satisfies a social need. The demand to use information systems that support the efficient development of processes in companies that provide transportation services has become a necessity, due to the fact that the execution of processes is done manually, resulting in inconveniences and inconsistencies when handling information and providing service to their customers. Performing manual records generates problems that can be easily observed such as the slowdown and mismanagement of processes, loss of information and little interaction with customers; reasons that create difficulties of access and communication. Consequently, the objective of this Degree Project (TT) is to optimize the processes in the modality of free contracting of the cab cooperative of interparochial transport of the city of Loja, using information technologies, with the purpose of facilitating a proposal that allows the use of an ERP system for the execution of the processes of this modality of the company in a modular way. In order to generate the automation proposal, three stages were approached, in the initial stage the company's requirements were obtained through information gathering techniques, in addition to the bibliographic compilation that allowed the selection of the Bonitasoft and Odoo tools for the documentation and implementation of processes. In the second stage, the MSSE methodologies were used for ERP selection, BPM:RAD for process documentation and AIM for the implementation of processes in the ERP. As a final stage, the proposed ERP system was validated by company personnel in a simulated test environment that allowed to determine the correct operation of the system according to the requirements and normal flow of processes with their respective optimizations. Therefore, the modules developed for implementation in the proposed Odoo ERP generate an optimal solution that solves the problems faced, providing an orderly and centralized management of information, optimized time and resources, the advantage of interaction with the customer and the reduction of economic costs. Facilitating future work to expand the functionality of the system focused on urban service or expansion to other platforms to facilitate access. Keywords: BPM, ERP, BPM:RAD, AIM, Information System, Bonitasoft, Odoo.